A methodology for managing public spaces to increase access to essential goods and services by vulnerable populations during the COVID-19 pandemic - Regal Ludowieg A. (2021)
The authors would like to acknowledge CONCYTEC's and FONDECYT's contribution to the development of this paper by providing crucial financial support under grant number E067-2020-02 (with registry number 72354). Bronfman gratefully acknowledges the support by the Research Center for Integrated Disaster Risk Management (CIGIDEN), ANID/FONDAP/15110017.